Fast laser Quantity Measurement of Pest Box Imaging Using End-to-End Real Time in Thai Rice Farm - Siriwan Polset; Chow Chompoo‐inwai (My University, 2021)
In this paper, the researcher development a fast laser quantity measurement of pest box imaging using end-to-end real time in Thai rice farm. Usage of a small, light, low-cost, high precision laser raining sensor for detected pests in rice farm and send number data to ESP32-CAM then it will take a pest box picture send to user application LINE. The processing can save statistical data from laser raining sensor on memory card of ESP32-CAM for quantity pests analysis. The researchers had designed pest measure box two sets and install in rice farm an area of 3.2 acre. The experiment is quantity measurement of pest box in the real environment of rice grow season in Thailand. Measurement were for 3 different period of time: rice seedlings to tillering stage (30 – 45 days old), rice at full tillering stage, pregnancy-to-earth rice. The results show a lot of pest the before harvest season is pregnancy to earth rice.
Keywords: Smart Agriculture and AI